Critical infrastructure protection : from cybersecurity to cyber resilience - Hassan, Aslinda (Penerbit UTeM, Press, Universiti Teknikal Malaysia Melaka, 2021)
Critical infrastructure systems (CISS) such as electric power systems and water supply systems are critical assets of cities and countries since they have a fundamental role in delivering commodities essential to various functions in daily human activities. They also include the critical information infrastructures, virtual or cyber systems, that increasingly support critical infrastructure sectors, such as energy systems, and daily activities, such as banking and communication. CISS are large and complex, which makes it unfeasible to consider all possible failure scenarios. It is then acknowledged that if total security cannot be achieved, more effort should be devoted to planning effective response and recovery. Subsequently, there has been a paradigm shift in recent years from risk and reliability concepts toward resilience concepts in CISS.